INFLIXIMAB IN TREATMENT OF REFRACTORY JUVENILE ARTHRITIS - I.P. Nikishina; S.R. Rodionovskaya; A.N. Shapovalenko; E.S. Fedorov; D.L. Alekseev (Вопросы современной педиатрии, 2010)
Inclusion to the clinical practice of genetically engineered biological medications opens new opportunities in treatment of juvenile arthritis. The article summarizes an experience of treatment of juvenile arthritis with infliximab in children’s department of Scientific Center of Rheumatology, Russian Academy of Medical Sciences. The analysis included 55 patients (16 children had systemic type, 23 — polyarticular type of juvenile arthritis, and 16 patients had juvenile spondylarthritis), treated with infliximab in 2002–2009 years. Infliximab was administrated in patients with high activity of the disease refractory to the modern basic therapy. Patients received intravenous infliximab 3–5 mg/kg daily according to the standard scheme (on 0, 2, 6 weeks and further every 8 weeks). Therapy with this drug was estimated as effective (improvement on 30% and more according ACRpedi) in 80% of patients: 16% achieved ACR30, 29% — ACR50, 26% — ACR70, and 9% — ACR90. Unfavorable effects (infusion reactions) were detected in 16% of cases. Infections, including one case of disseminated tuberculosis, developed in 20% of patients. Thus, treatment with infliximab is effective and has good «risk–benefit» ratio in treatment of patients with refractory juvenile arthritis. Key words: children, juvenile arthritis, infliximab, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(1):142-149)